Clock in : No-BS advice for getting ahead in your career (without losing your mind) - Durham, Emily (Tarcher, an imprint of Penguin Random House, 2026)
Did you know the average job search takes more than five months? That's because today's job market is more challenging--and more confusing--than ever. How are we supposed to get hired, get paid, and get ahead in our careers? Why is everything so complicated and gatekept? That's where Emily the Recruiter comes in. Using her years of experience as a recruiter and career coach, she pulls back the curtain on everything employment-related and tells you all you need to know about job hunting, networking, and not letting your boss drive you crazy. A much-needed antidote to the "gaslight, gatekeep, girlboss" ethos, this guidebook gives you the real talk you need to lock in when you clock in. If you're ready to work smarter, not harder, Clock In is the no-filter, no-fluff resource you need to thrive in your nine-to-five--and beyond. --